SOCIAL MEDIA IN GUIDING AND MARKETING RELIGIOUS TOURISM: THE CASE OF UMRAH AND HAJJ SERVICES - Ute Lies Siti Khadijah; Evi Novianti; Rully Anwar (Universitas Padjadjaran, 2022)
The media played a central role in communication between people, including religious matters. In religious tourism, there were scouting activities between the committee, ustadz, and congregation in the context of worship that was carried out well. The most prominent in this religious tourism was the pilgrimage and umrah. Thus, there were many Hajj and Umrah communities in a Muslim-majority country like Indonesia. This study aims to determine the role of social media in religious tourism guidance and marketing activities. This study used a micro-sociological analysis of qualitative data from activities at one of the Hajj and Umrah guidance centers in Bandung, Indonesia. Using social network analysis, it was found that social media’s role was essential to disseminate information between Hajj and Umrah guidance institutions and their congregations. The use of Facebook for the profile of the guidance institution was beneficial for pilgrims to understand the various opportunities and obstacles that exist in the Hajj/Umrah pilgrimage. WhatsApp was the most frequently used to communicate interactively with the congregation so the clerics and committees. Social media is quite helpful in marketing when the assembly connects with friends and family in telling their experiences when worshiping in Mecca and Medina in Saudi Arabia.